The Mitochondrial Genome of a Plant Fungal Pathogen Pseudocercospora fijiensis (Mycosphaerellaceae), Comparative Analysis and Diversification Times of the Sigatoka Disease Complex Using Fossil Calibrated Phylogenies - Juliana E. Arcila-Galvis; Rafael E. Arango; Javier M. Torres-Bonilla; Tatiana Arias (Life, 2021)
Mycosphaerellaceae is a highly diverse fungal family containing a variety of pathogens affecting many economically important crops. Mitochondria play a crucial role in fungal metabolism and in the study of fungal evolution. This study aims to: (i) describe the mitochondrial genome of Pseudocercospora fijiensis, and (ii) compare it with closely related species (Sphaerulina musiva, S. populicola, P. musae and P. eumusae) available online, paying particular attention to the Sigatoka disease’s complex causal agents. The mitochondrial genome of P. fijiensis is a circular molecule of 74,089 bp containing typical genes coding for the 14 proteins related to oxidative phosphorylation, 2 rRNA genes and a set of 38 tRNAs. P. fijiensis mitogenome has two truncated cox1 copies, and bicistronic transcription of nad2-nad3 and atp6-atp8 confirmed experimentally. Comparative analysis revealed high variability in size and gene order among selected Mycosphaerellaceae mitogenomes likely to be due to rearrangements caused by mobile intron invasion. Using fossil calibrated Bayesian phylogenies, we found later diversification times for Mycosphaerellaceae (66.6 MYA) and the Sigatoka disease complex causal agents, compared to previous strict molecular clock studies. An early divergent Pseudocercospora fijiensis split from the sister species P. musae + P. eumusae 13.31 MYA while their sister group, the sister species P. eumusae and P. musae, split from their shared common ancestor in the late Miocene 8.22 MYA. This newly dated phylogeny suggests that species belonging to the Sigatoka disease complex originated after wild relatives of domesticated bananas (section Eumusae; 27.9 MYA). During this time frame, mitochondrial genomes expanded significantly, possibly due to invasions of introns into different electron transport chain genes.